01 Lambeth Conventions update: the agenda. Issue 1 (10th December 2010) - Curtis, M J
Abstract : The advances made in pharmacotherapy of cardiac arrhythmias in the last 20 years have been disappointingly meagre. The Lambeth Conventions (Walker et al, 1988) is a guidance for (ventricular) arrhythmia research. It was published more than 20 years ago. It has provided a framework for disciplined experimentation and offers immutable guidance on experimental practice (use of blinding and randomisation, selection of controls, etc.) but it requires an update. It is clear that the community needs to refocus on how new anti-arrhythmic drugs will be found. We need to reappraise the available models and approaches. We need to expand the Lambeth Conventions guidance to cover all types of arrhythmias. We need to elaborate guidance for the study of proarrhythmia (eg, Torsades de Pointes) and consider guidance for interrogating and targeting channelopathy. On September 6 and 7, 2010, invited and freely registered participants will consider a series of lecture presentations and engage in discussions that will inform the preparation of a new Lambeth Conventions guidance.